Short-term responses of the field layer vegetation in a south Swedish deciduous forest after establishment of wild boars (Sus scrofa) - Wahlgren, Emmelie (2015)
Inside the south Swedish national park Dalby Söderskog, wild boars (Sus scrofa L.) have been visiting since 2010. The presence of wild boars has earlier been proven to impact both soil and vegetation characteristics, both positively and negatively. Still, there is a lack of knowledge regarding the rooting effect on the vegetation in deciduous forest within the native range. In this study, I have compared the field vegetation collected before and after the invasion of wild boars in 74 permanent experimental plots. More specifically, the study aimed to qualify the effect of wild boar rooting on cover ratio, species richness and species composition in a temperate deciduous forest. The rooting frequency did increase from 0% in 2010 to 61% in 2013. The results indicated a general cover loss of both spring vegetation (-40%) and summer vegetation (-30%). Within the rooted areas, cover ratio of the dominant spring flowers Anemone nemorosa (wood anemone), Anemone ranunculoides (yellow) and Ranunculus ficaria (lesser celandine) decreased from 60 % to 33 %. The total species number increased from 44 to 45 and the average species richness increased from 6.3 to 6.9 species/m3. In conclusion, wild boars seem to cause heavy damages on the cover ratios. Rooting appears to favour small and non-competitive species, but also to increase the species richness. Even tough most of the results are in line with previous studies, it is more preferable to consider them as indications of short-term effects as the time aspect is as short as three years.